Contraception and Reproductive Medicine - Shoupe, Donna; Christy, Alicia; SpringerLink (Online service) (London : BioMed Central : Imprint: BioMed Central.)
Contraception and Reproductive Medicine is an online, open-access, peer reviewed journal that is designed to promote the advancement of contraceptive technology particularly in the areas of education, effectiveness, safety, research interest, improved or new technologies, non-contraceptive benefits, and long-term health. The journal publishes articles on all areas of female and male contraceptive technology, clinical and basic trials, meta-analyses, reviews, international submissions, and editorials. All manuscripts submitted to Contraception and Reproductive Medicine should adhere to BioMed Central's editorial policies.
Keywords: Reproductive medicine; Reproductive Medicine